1995
DOI: 10.1099/00207713-45-4-811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mycobacterium 23S rRNA Sequences by High-Temperature Reverse Transcription and PCR

Abstract: We describe a modified rRNA sequence analysis method which we used to determine the phylogenetic relationships among 58 species belonging to the genus Mycobacterium. We combined the sensitivity of the reverse transcriptase PCR for amplifying nanogram amounts of template rRNA material with the elevated extension temperatures used for the thermostable DNA polymerase from Thermus thermophilus. A 70°C reverse transcription extension step permitted improved read-through of highly structured rRNA templates from memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…However, when previously tested in the manual format, M. africanum gave positive results similar to those obtained with other M. tuberculosis complex organisms (39). These results are consistent with the observation that the target regions of both M. africanum and M. microti rRNA to which the capture probe binds differ from the M. tuberculosis target sequence by only one nucleotide (43).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, when previously tested in the manual format, M. africanum gave positive results similar to those obtained with other M. tuberculosis complex organisms (39). These results are consistent with the observation that the target regions of both M. africanum and M. microti rRNA to which the capture probe binds differ from the M. tuberculosis target sequence by only one nucleotide (43).…”
Section: Discussionsupporting
confidence: 85%
“…Previously, inclusivity testing of all five M. tuberculosis complex members showed that M. bovis and M. tuberculosis strains were detected by hybridization and Q-Beta replicase amplification, as predicted by sequence data (43). When multiple samples of 10-fold dilutions of nine M. tuberculosis strains were tested, the lower limit of detection was determined to be Ͻ10 to 300 CFU.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Primer 3,5'-CCG TGA GGG AAA GGT GAA AAG TAC C-3', which corresponds to the sequence from 461 to 485 bp in the Escherichia coli nomenclature, was designed during this work. It is a slight modification of primer 3415 (26). Primer 4,5'-CCC GCT TAG ATG CTT TCA GC-3', which corresponds to sequence from 2744 to 2763 bp in the E. coli nomenclature, was described by Van Camp et al (7) as 97ar.…”
Section: Methodsmentioning
confidence: 99%
“…One M. smegmatis isolate was misidentified as M. fortuitum II by the GenoType. A possible explanation for this identification mistake is the high degree of homology in the 23S rRNA sequence for these two mycobacterial species (20). Interestingly, one other M. smegmatis isolate was correctly identified by GenoType as nontuberculous mycobacteria.…”
Section: Discussionmentioning
confidence: 98%